The authorities of Senegal must immediately halt the police violence and restore social media - Amnesty International (Amnesty International, 2023)
Reacting to the violence that broke out yesterday in Dakar and other towns following the verdict in the trial of opposition leader Ousmane Sonko, Samira Daoud, Amnesty International’s Regional Director for West and Central Africa
Keywords: 2023-06 June